Determination of the probability and rate of corrosion on reinforced - Bernal Castillo, Fredy; Roa Rodríguez, Guillermo; Cabrera Cabrera, Carlos; Sierra Melo, Nicolás; Aperador, William (TECCIENCIA, 2015)
In this paper, we present the design and construction of a remote monitoring system for determining the probability and rate of corrosion of rebar embedded in concrete. We use the ASTM standard C876 technique for the probability of corrosion and the Linear Polarization Resistance method to indirectly obtain the rate of corrosion. The system consists of a communication module using GSM and GPRS cellular networks which provide remote measurements. The device was used to evaluate corrosion with reference electrodes of copper/copper sulfate and graphite on Type I Portland cement specimens of 15cm in diameter and 30cm in length. The results of the measurements were compared to a commercial system, revealing similar values to the data obtained in the field and the laboratory.